2019
DOI: 10.1111/os.12464
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D‐printed Customized Guides in Subtalar Joint Arthrodesis

Abstract: Objective To explore the feasibility of 3D printed customized guides assisting the precise drilling of Kirschner wires in subtalar joint arthrodesis. Methods We retrospectively reviewed the data of 29 patients (30 subtalar joints) who underwent subtalar joint arthrodesis between 1 July 2013 and 31 December 2017. The customized guides were designed on a full‐scale 3D polylactic acid model made from computed tomography (CT) data of patients by Model Intestinal Microflora in Computer Simulation (MIMICS) software,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…activity limitation and support requirement, maximum walking distance, walking surfaces, gait abnormality, sagittal motion, hindfoot motion, and ankle stability), and 10 points of alignment [36]. Duan et al [23] demonstrated comparable AOFAS scores between the 3DPM and control group in the treatment of ankle deformities. In the study by Zhang et al [35], comparable AOFAS scores between the 3D printing group and the conventional group (87.4 vs. 84.7) were noted.…”
Section: Aofasmentioning
confidence: 99%
See 2 more Smart Citations
“…activity limitation and support requirement, maximum walking distance, walking surfaces, gait abnormality, sagittal motion, hindfoot motion, and ankle stability), and 10 points of alignment [36]. Duan et al [23] demonstrated comparable AOFAS scores between the 3DPM and control group in the treatment of ankle deformities. In the study by Zhang et al [35], comparable AOFAS scores between the 3D printing group and the conventional group (87.4 vs. 84.7) were noted.…”
Section: Aofasmentioning
confidence: 99%
“…Previous studies have shown that the use of 3DPM is associated with decreased surgical time and intraoperative X-ray exposure, as well as increased operative accuracy and safety compared to traditional imaging in the treatment of ankle deformities [21,22]. Duan et al [23] found that preoperative planning with 3DPM facilitated accurate drilling of K-wires into the appropriate position, reduced the operation time and intraoperative radiation in 29 patients who underwent subtalar joint arthrodesis. A randomized controlled trial by Zheng et al [24] showed that 3DPMassisted surgical planning had shorter operation duration, less blood loss and X-ray exposure, as well as better anatomic reduction and clinical outcomes than conventional surgery in 100 patient with Pilon fractures.…”
Section: D Printed Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that patient specific instrumentation is accurate and reproducible performing total ankle arthroplasty [10,11]. 3D printed custom guides have also been designed for subtalar joint arthrodesis, and a recently published study found that these guides reduced operative time and radiation exposure from fluoroscopy [12].…”
Section: D Printing In Foot and Ankle Surgerymentioning
confidence: 99%
“…However, they do not actually address the deformity of the subtalar joint complex, and patients are faced with the risk of nonunion or malunion and a longer recovery time. Arthrodesis should be avoided if at all possible because of the loss of the shock‐absorbing function of the subtalar joint complex and the tendency to develop early degenerative arthritis in adjacent joints 4–6 . STA refers to the implantation of a device in the sinus tarsi to restrict excessive eversion of the subtalar joint and consequently correct the flatfoot deformity.…”
Section: Introductionmentioning
confidence: 99%